Does Banking Performance Matter for Stock Prices? Post-Merger Evidence from Bank Syariah Indonesia - Iis Wahyuni; Toni Andrianto; Abdul Roup; Nilda Tartila (Institut Bisnis dan Informatika Kesatuan, 2025)
This study examines the impact of banking performance on the stock price of Bank Syariah Indonesia (BSI) in the post-merger period. The merger of three state-owned Islamic banks into BSI represents a strategic consolidation aimed at strengthening competitiveness, efficiency, and market value within Indonesia’s Islamic banking sector. Using a quantitative and explanatory research design, this study analyzes secondary data derived from BSI’s financial statements and stock price data during the post-merger period from 2021 to 2024. Banking performance is measured using profitability (ROA and ROE), asset quality (Non-Performing Financing/NPF), liquidity (Financing to Deposit Ratio/FDR), capital adequacy (CAR), and efficiency (BOPO). Multiple linear regression analysis is employed to examine the relationship between banking performance indicators and stock price movements. The results indicate that profitability, asset quality, capital adequacy, and efficiency have a significant effect on BSI’s stock price, while liquidity shows a weaker and less consistent influence. Among the examined variables, profitability and efficiency emerge as the most dominant determinants of stock price movements, suggesting that investors place greater emphasis on earnings capacity and operational effectiveness in evaluating post-merger performance. These findings imply that the success of banking consolidation in Islamic banking is reflected not merely in organizational scale but in tangible improvements in financial performance that are recognized by the capital market. The study provides valuable insights for bank management, investors, and policymakers regarding post-merger performance evaluation and consolidation strategies in Islamic banking. Keywords: Islamic banking, merger, banking performance, stock price, Bank Syariah Indonesia.